2018
DOI: 10.15761/cmid.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous diagnosis of tuberculous and non-tuberculous mycobacterial diseases: Time for a better patient management

Abstract: Tuberculosis (TB) is the deadliest infectious disease in the world which disproportionately affects low-and-middle-income countries (LMICs) where diagnostic resources and treatment options are limited. The incidence of pulmonary non-tuberculous mycobacteria (NTM) disease is also rapidly increasing in these regions traditionally dominated by TB infections. This poses significant diagnostic and treatment challenges, since these two diseases are often indistinguishable clinically or by sputum smear microscopy (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…23 Reports from the literature as well as our findings suggest the need for increased clinical awareness as to the possibility of co-existing MTB and NTM infections.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…23 Reports from the literature as well as our findings suggest the need for increased clinical awareness as to the possibility of co-existing MTB and NTM infections.…”
Section: Discussionsupporting
confidence: 52%
“…These are two different pathogens that have many similar clinical and epidemiological features but that have different treatment regimens. 23…”
Section: Discussionmentioning
confidence: 99%
“…NTM are generally environmental bacteria, so it is reasonable that specific environmental factors relating to soil, water, and temperature can affect the distribution of NTM species and the risk of NTM disease, leading to specific geographic characteristics and time variation. Research showed that MAC was the most common species worldwide, accounting for 34–61% of all NTM isolates ( 19 ), followed by M. gordonae, M. xenopi , and M. kansasii , and M. fortuitum was the most common rapid mycobacterial grower ( 20 ). Regional analyses showed that M. kansasii was the most common species in Slovakia and Poland, M. xenopi in Central, Southern, and Western Europe, M. malmoense in Northern Europe, and M. abscessus complex in North America, Taiwan, Australia, and South Korea ( 19 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In high tuberculosis (TB)-burden countries, diagnosis of NTM is rarely made because of lack of awareness among healthcare providers about the NTM diseases and poor access to adequate laboratory resources including mycobacterial culture and molecular methods for identification or speciation 10 . In these resource-limited settings, there is a heavy reliance on smear microscopy for the diagnosis of TB, and the diagnosis of NTM is frequently missed and these patients are empirically treated as drug-sensitive and -resistant TB 11 .…”
Section: Introductionmentioning
confidence: 99%